2020
DOI: 10.3390/app10175793
|View full text |Cite
|
Sign up to set email alerts
|

Tooth Discoloration after Regenerative Endodontic Procedures with Calcium Silicate-Based Cements—An Ex Vivo Study

Abstract: The aim of the present ex vivo study was to assess and compare coronal discoloration induced by four endodontic biomaterials used in regenerative endodontic procedures (REPs). Root resection was executed horizontally, 2 mm apical to the cementoenamel junction, in all fifty-four teeth. After accessing the pulp chamber, specimens were randomly divided in groups and filled with either saline solution or blood, followed by calcium silicate-based cements (CSCs) placement: ProRoot mineral trioxide aggregate (MTA) (D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
61
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(65 citation statements)
references
References 31 publications
4
61
0
Order By: Relevance
“…White MTA has been reported to cause discoloration due to the presence of the bismuth oxide radiopacifier, requiring a search for alternatives. Mixing results in a grainy mass that is difficult to introduce and condense at the exposure site [3,[10][11][12][13][14][15][16][17][18].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…White MTA has been reported to cause discoloration due to the presence of the bismuth oxide radiopacifier, requiring a search for alternatives. Mixing results in a grainy mass that is difficult to introduce and condense at the exposure site [3,[10][11][12][13][14][15][16][17][18].…”
Section: Discussionmentioning
confidence: 99%
“…It is widely used in pediatric dentistry due to its excellent sealing properties. Its disadvantages include slow setting time, difficulty in handling and tooth staining [10][11][12][13][14][15][16].…”
Section: Antimicrobialmentioning
confidence: 99%
“…This undesirable outcome may be caused by the use of calcium silicate cements in the apexification procedure [ 34 , 35 ], when they contain bismuth oxide as a radiopacifier [ 34 , 35 , 36 ]. The proper choice and the way to use a Portland cement may reduce the chances of this aesthetic consequence [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…Different studies claim that discoloration of composite cements used in endodontic procedures is the major limitation for these kinds of materials [ 35 , 61 , 62 ]. Even if composite loaded with bismuth oxide filler showed negligible discoloration over time [ 63 ], a recent study reported that in particular conditions the discoloration in the long period could be significant [ 64 ].…”
Section: Discussionmentioning
confidence: 99%